2019
DOI: 10.1089/wound.2018.0832
|View full text |Cite
|
Sign up to set email alerts
|

Instillation Negative Pressure Wound Therapy: A Role for Infected LVAD Salvage

Abstract: Objective: To determine the utility of instillation negative pressure wound therapy (NPWT) in achieving eradication of infection and definitive wound closure in patients with infected left ventricular assist device (LVAD). Approach: A retrospective review was performed in a series of patients with infected and exposed LVADs who were treated with instillation NPWT in conjunction with surgical debridement. Results: Three consecutive patients were included who developed periprosthetic infection subsequent to LVAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Our primary endpoint is the retention of metalwork and resolution of active infection, allowing fracture union; our present cohort has shown a 96% success rate, reflecting the 100% success rate in the previous cohort (n = 16) [6]. Reviews of the literature have shown largely 100% success rates from case series using NPWT instillation focussing on implant salvage in extremity wounds (n = 4) [8], spinal wounds (n = 3) [9] and infected left ventricular assist devices (n = 3) [10]. A recent retrospective review (n = 28) showed 89% successful retention or replacement of implants of mixed locations (spinal, sternal and extremity), and specifically 61% success in original implant retention [7].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our primary endpoint is the retention of metalwork and resolution of active infection, allowing fracture union; our present cohort has shown a 96% success rate, reflecting the 100% success rate in the previous cohort (n = 16) [6]. Reviews of the literature have shown largely 100% success rates from case series using NPWT instillation focussing on implant salvage in extremity wounds (n = 4) [8], spinal wounds (n = 3) [9] and infected left ventricular assist devices (n = 3) [10]. A recent retrospective review (n = 28) showed 89% successful retention or replacement of implants of mixed locations (spinal, sternal and extremity), and specifically 61% success in original implant retention [7].…”
Section: Discussionsupporting
confidence: 52%
“…Finally, testing the reproducibility of any novel techniques is an important step as is the present study. While numerous variations of NPWT have been independently tested in the literature [7][8][9][10][11] to produce implant salvage, rigorous testing of one technique is rare. We reproduced similar results as the previous cohort in a different location [6], which reconfirms the data.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, use of NPWT in infected wounds has been limited. However, the addition of a regular and automatically instilled topical solution over the wound during NPWT has been reported to reduce bioburden levels compared with standard NPWT alone in multiple clinical and scientific studies 6‐10 …”
Section: Introductionmentioning
confidence: 99%
“…wound during NPWT has been reported to reduce bioburden levels compared with standard NPWT alone in multiple clinical and scientific studies. [6][7][8][9][10] The presence of bacteria in wounds is known as a significant factor that can delay healing. While infections of the deep and surrounding compartments require systemic treatment, wound-related bacterial damage occurs on the surface and can be treated topically.…”
mentioning
confidence: 99%
“…Short-term mechanical circulatory support, including extracorporeal ventricular assist device (VAD), is still a realistic option to reverse refractory cardiogenic shock, to ameliorate secondary organ failures, and to provide bridges to the next therapeutic stages [1], urgent heart transplantation or implantable VAD. Infection is a serious complication of extracorporeal VAD use with high mortality and difficulty to treat due to biofilm formation on the device surfaces, making bacteria less susceptible to antibiotics [2]. In this report, we describe prophylactic management of the cannula sites with a vacuum-assisted closure (VAC) system (KCI Inc, San Antonio, TX) in a patient supported by extracorporeal biventricular assist devices (BiVADs) for more than 9 months.…”
Section: Introductionmentioning
confidence: 99%